2009
DOI: 10.1007/s12229-009-9031-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signalling In Plants

Abstract: Nitric oxide (NO) is an important molecule that acts in many tissues to regulate a diverse range of physiological processes. It is becoming apparent that NO is a ubiquitous signal in plants. Since the discovery of NO emission by plants in the 1970s, this gaseous compound has emerged as a major signalling molecule involved in multiple physiological functions. Research on NO in plants has gained significant awareness in recent years and there is increasing indication on the role of this molecule as a key-signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 165 publications
(201 reference statements)
0
32
1
Order By: Relevance
“…Recently, an increasing number of articles have reported the effects of exogenous NO on alleviating HM toxicity in various plants (Jin et al 2010;Xiong et al 2010;Panda et al 2011). Evidence has been obtained for the relation of NO and plant growth regulators (Palavan-Unsal & Arisan 2009;Yadav et al 2011;Shen et al 2013). However, there are not any studies that have identified the effects of TRIA and NO on stress-induced changes in the antioxidative defense system in plants under HM stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of articles have reported the effects of exogenous NO on alleviating HM toxicity in various plants (Jin et al 2010;Xiong et al 2010;Panda et al 2011). Evidence has been obtained for the relation of NO and plant growth regulators (Palavan-Unsal & Arisan 2009;Yadav et al 2011;Shen et al 2013). However, there are not any studies that have identified the effects of TRIA and NO on stress-induced changes in the antioxidative defense system in plants under HM stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), a gaseous free radical, is involved in numerous physiological processes in plants, including plant responses to biotic and abiotic stress (Wojtaszek 2000;Lamotte et al 2005;Palavan-Unsal and Arisan 2009;Misra et al 2010;Scheler et al 2013;Trapet et al 2014). Indications that NO is involved in signaling defense responses during plant-pathogen interactions are well documented (Sudha and Ravishankar 2002;Arasimowicz and Floryszak-Wieczorek 2007;Zhang et al 2012;Scheler et al 2013;Yu et al 2014;Trapet et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the cytochrome P450 enzymes play a major role in one of the nitric oxide (NO) biosynthetic pathways, catalyzing the oxidation of N-hydroxyguanidines and the formation of nitrogen oxides, including NO (39). NO signaling has been found to be involved in the induction of cell death and in interactions with ROS (44), and several studies have reported links between NO synthesis and the breakdown of a cnidarian-alga symbiosis (8,45,67). Also, ROS generated during thermal stress in symbiotic dinoflagellates (16,41) has been related to coral bleaching (38,50,73).…”
mentioning
confidence: 99%